Transport in Shale Reservoirs - Lee, Kun Sang; Lee, Kun Sang; Kim, Tae Hong (Gulf Professional Publishing, 2019)
Transport in Shale Reservoirs fills the need for a necessary, integrative approach on shale reservoirs. It delivers both the fundamental theories of transport in shale reservoirs and the most recent advancements in the recovery of shale oil and gas in one convenient reference. Shale reservoirs have distinctive features dissimilar to those of conventional reservoirs, thus an accurate evaluation on the behavior of shale gas reservoirs requires an integrated understanding on their characteristics and the transport of reservoir and fluids. - Updates on the various transport mechanisms in shale, such as molecular diffusion and phase behavior in nano-pores - Applies theory to practice through simulation in both shale oil and gas - Presents an up-to-date reference on remaining challenges, such as organic material in the shale simulation and multicomponent transport in CO2 injection processes